Exploring agro-ecological bases of contemporary water management innovations (CWMIs) and their outscaling - GUPTA, SANJAY KUMAR; RAO, D U M; NAIN, M S; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2021)
Innovations related to judicious use of scarce water resources evolved by farmers and refined by non-formal researchers termed as Contemporary Water Management Innovations (CWMIs) are now being practiced in drylands by majority of farmers in India for human and crop survival during water crisis. The study was carried out during 2017-18 in purposively selected villages of Ananthapur district of Andhra Pradesh. A sample of 120 (farmers) and 30 (mixed group of scientist’s, NGOs activist and other experts) were selected randomly on the basis of the presence of and association with functional water sharing groups (WSGs). For critical analysis, a combination of focused group discussions, case study and Delphi technique accompanied by knowledge index, adoption index, multiple regression, correlation and factor analysis were used. It was found that only 20 users owned bore wells and shared with 100 farmers who did not own any bore wells. CWMI were well accepted and integrated into the culture of the dryland farmers as they comprehensively understood the agro-ecological bases for their survival and sustenance in dry land areas. 14 factors were deduced for agro ecological crises, Majority (63.33%) of farmers possessed high level of knowledge about the agro-ecological reasons behind the CWMIs and 60.83% of farmers had high (70â€“86%) extent of adoption of all the CWMIs and 65.8% of farmers had adopted 12 out of the 14 different practices. Need for synergy and convergence among researchers, administrations, line departments, NGOs, extension system were felt as the facilitative factors for diffusing CWMIs.